A mineral-based all-solid electrolyte and its preparation method and application

By using mineral-based all-solid electrolytes, the capacity attenuation problems caused by the dissolution of negative iodine positive electrode, shuttled through multiple iodides and side reactions of zinc negative electrodes in aqueous solution are solved, and the battery capacity is maintained for a long time and the stability of zinc negative electrodes are achieved.

CN118610611BActive Publication Date: 2025-03-21HAINAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410858888.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-28
Publication Date
2025-03-21
Estimated Expiration
2044-06-28

AI Technical Summary

Technical Problem

Due to the dissolution of the negative iodine positive electrode, the shuttle of polyiodide and the side reaction of the zinc negative electrode in the aqueous solution, the rapid attenuation of capacity and corrosion of the zinc negative electrode, the large-scale commercialization and industrialization are restricted.

Method used

The mineral-based all-solid electrolyte is prepared by mixing mullite powder with zinc salt electrolyte, ultrasonic and stirring, and centrifugal washing and drying. The electrolyte is stable itself, inhibiting the side reactions caused by active water, and strongly adsorbing polyiodide through rich silicon oxygen and aluminum oxygen bonds to prevent it from shuttle.

Benefits of technology

It effectively avoids side reactions of zinc negative electrodes and shuttles of polyiodides, extends the cycle stability of battery capacity, and improves the cycle stability and corrosion resistance of zinc-iodine batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118610611B_ABST
    Figure CN118610611B_ABST
Patent Text Reader

Abstract

The embodiments of the present application relate to a mineral-based all-solid electrolyte and its preparation method and application, which belongs to the technical field of aqueous zinc ion battery electrolyte preparation. The preparation method of the mineral-based all-solid electrolyte of the embodiment of the present application comprises the following steps: mixing mullite powder with a zinc salt electrolyte, performing ultrasonic and stirring treatment, and obtaining a mineral-based all-solid electrolyte after centrifugal washing and drying. The mineral-based all-solid electrolyte provided in the embodiment of the present application can not only avoid the side reactions caused by active water, but also inhibit the shuttling of polyiodides in the negative iodine positive electrode, avoid the attenuation of the battery capacity and the corrosion of the zinc negative electrode by the shuttling of polyiodides, and has a good application prospect in aqueous zinc ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present application relate to the technical field of aqueous zinc ion battery electrolyte preparation, and in particular to a mineral-based all-solid-state electrolyte and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries have dominated energy storage for decades, but the scarcity of lithium metal has led to high production costs, making the large-scale application of lithium-ion batteries face severe challenges. Compared with lithium-ion batteries, the most obvious advantage of aqueous zinc-ion batteries is their low price, which is particularly suitable for large-scale energy storage systems. In particular, zinc-iodine batteries are expected to become the mainstay of future energy storage systems due to their high energy density, long life, and safety. However, in aqueous solutions, the large-scale commercialization and industrialization of zinc-iodine batteries are limited by problems such as the dissolution of the negative iodine positive electrode, the shuttling of multiple iodides, and a large number of side reactions at the zinc negative electrode.

[0003] In order to solve the above problems, many researchers have proposed various feasible solutions. For example, an in-situ or non-in-situ protective layer is cast on the zinc negative electrode to prevent the zinc metal from directly contacting the electrolyte. Although this greatly reduces the side reactions of the zinc negative electrode, it cannot change the problem of rapid capacity decay caused by the dissolution of iodine and the shuttling of polyiodides. For another example, the use of porous catalytically active materials for iodine fixation can not only increase the iodine loading, so that the battery has a high specific capacity, but also catalyze the reaction and reduce the production of polyiodides. However, it cannot change the dissolution of iodine in aqueous solution and the occurrence of side reactions of the zinc negative electrode. Summary of the invention

[0004] In view of this, the embodiments of the present application provide a mineral-based all-solid-state electrolyte and a preparation method and application thereof. The mineral-based all-solid-state electrolyte can not only avoid the side reactions caused by active water, but also inhibit the shuttling of polyiodides between the negative iodine positive electrode and the negative iodine positive electrode, thereby avoiding the attenuation of the battery capacity and the corrosion of the zinc negative electrode by the shuttling of polyiodides. It has a good application prospect in aqueous zinc-ion batteries and can effectively overcome the defects of the above-mentioned prior art.

[0005] A first aspect of an embodiment of the present application provides a method for preparing a mineral-based all-solid electrolyte, comprising the following steps:

[0006] The mullite powder is mixed with the zinc salt electrolyte, subjected to ultrasonic and stirring treatment, and then centrifugally washed and dried to obtain a mineral-based all-solid electrolyte.

[0007] In some embodiments that may include the above embodiments, the ultrasonic time is 0.5 to 3 hours, and the stirring time is 4 to 24 hours.

[0008] In some embodiments that may include the above embodiments, the washing times are 2 to 4 times; the drying time is 6 to 12 hours, and the drying temperature is 60 to 100°C.

[0009] In some embodiments that may include the above embodiments, the mass volume ratio of the mullite powder and the zinc salt electrolyte is (1-3.5):(5-15).

[0010] In some embodiments that may include the above embodiments, the zinc salt electrolyte is at least one of a zinc sulfate electrolyte, a zinc trifluoromethanesulfonate electrolyte, a zinc acetate electrolyte, a zinc nitrate electrolyte, and a zinc chloride electrolyte; or

[0011] The zinc salt electrolyte has a concentration of 1 to 3 mol / L. Preferably, the amount of the zinc salt electrolyte added is 10 μl to 50 μl.

[0012] In some embodiments that may include the above embodiments, the following steps are also included:

[0013] The mineral-based all-solid electrolyte is weighed and tableted using a tablet press to obtain a stable sheet-like mineral-based all-solid electrolyte.

[0014] Preferably, the mass of the mineral-based all-solid electrolyte is weighed to be 0.08-0.25 g.

[0015] In some embodiments that may include the above embodiments, the tablet pressing pressure of the tablet press is 15 to 30 MPa.

[0016] A second aspect of the embodiments of the present application also provides a mineral-based all-solid-state electrolyte prepared by the above-mentioned preparation method.

[0017] A third aspect of the embodiments of the present application also provides the use of the above-mentioned mineral-based all-solid-state electrolyte in the preparation of an aqueous zinc ion battery.

[0018] The fourth aspect of the embodiment of the present application also provides an aqueous zinc ion battery, which includes a battery housing and a positive electrode, a diaphragm and a negative electrode located in the battery housing, wherein the diaphragm is the above-mentioned mineral-based all-solid electrolyte.

[0019] Preferably, a zinc-zinc symmetrical battery is assembled from a sheet-like mineral-based all-solid electrolyte, a trace zinc salt electrolyte, a zinc sheet and a battery casing.

[0020] Preferably, a half-cell is assembled from a sheet-like mineral-based all-solid electrolyte, a trace amount of zinc salt electrolyte, a zinc sheet, a commercial current collector and a battery casing.

[0021] Preferably, the zinc-iodine full battery is assembled from a flaky mineral-based all-solid electrolyte, a trace zinc salt electrolyte, a zinc negative electrode, a negative iodine positive electrode and a battery shell.

[0022] Compared with the prior art, the embodiments of the present application have the following beneficial effects:

[0023] (1) The mineral-based all-solid electrolyte prepared in the embodiments of the present application has stable chemical properties and will not cause side reactions with the positive electrode or the negative electrode.

[0024] (2) The mineral-based all-solid electrolyte prepared in the embodiment of the present application has very little active water content, which effectively reduces the side reactions such as hydrogen evolution and oxygen evolution of the zinc metal negative electrode, widens the electrochemical window of the battery, and can guide the uniform deposition of zinc ions.

[0025] (3) The mineral-based all-solid-state electrolyte prepared in the embodiment of the present application contains rich silicon-oxygen and aluminum-oxygen bonds, has a strong adsorption effect on polyiodides, limits the shuttling effect of polyiodides, avoids their corrosion to the zinc negative electrode and the overall capacity decay of the zinc-iodine battery, and endows the zinc-iodine battery with excellent cycle stability.

[0026] (4) The preparation process of the embodiment of the present application is simple, the raw materials are widely available, it is green and environmentally friendly, and the production cost is low. Its large-scale application can promote the practical application of zinc-iodine batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0028] Figure 1 This is a comparison chart of the cycle performance of a zinc-iodine full battery assembled with the mineral-based all-solid electrolyte in Example 1 and 2 mol / L zinc sulfate at a current density of 1 A / g;

[0029] Figure 2 The zinc-zinc symmetric battery assembled with the mineral-based all-solid electrolyte in Example 1 and 2 mol / L zinc sulfate was 0.5 mA / cm 2 XRD comparison diagram of zinc sheet after 50 cycles under charge and discharge conditions;

[0030] Figure 3 This is a comparison diagram of the LSV test of the zinc-titanium half-cell assembled with the mineral-based all-solid electrolyte in Example 2 and 2 mol / L zinc sulfate;

[0031] Figure 4 This is a comparison diagram of the Tafel test of a zinc-zinc symmetrical battery assembled with the mineral-based all-solid electrolyte in Example 4 and 2 mol / L zinc sulfate;

[0032] Figure 5 The zinc-zinc symmetric battery assembled with the mineral-based all-solid electrolyte in Example 1 and 2 mol / L zinc sulfate was 0.5 mA / cm 2 SEM comparison of the zinc sheet after 50 cycles under charge and discharge conditions. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0034] Unless otherwise specified, the experimental methods used in the examples of this application are all conventional methods.

[0035] In the following examples and comparative examples, unless otherwise specified, all raw materials can be obtained by commercial purchase or conventional methods.

[0036] Example 1

[0037] The method for preparing the mineral-based all-solid electrolyte in this embodiment comprises the following steps:

[0038] Zinc salt electrolyte preparation: dissolve zinc sulfate in deionized water to prepare a zinc sulfate electrolyte with a concentration of 2 mol / L;

[0039] The mullite powder was added into a 2 mol / L zinc sulfate electrolyte at a mass volume ratio of 1:12.5, ultrasonicated for 1 hour, stirred for 6 hours, and then centrifuged, washed twice with deionized water, and then dried at 60°C for 12 hours to obtain a mineral-based all-solid electrolyte powder;

[0040] The mineral-based all-solid-state electrolyte powder was ground into fine powder in a mortar, 0.1 g of the fine powdered mineral-based all-solid-state electrolyte was weighed, and pressed into 0.3 mm thin sheets of mineral-based all-solid-state electrolyte at a tableting pressure of 20 MPa using a tablet press, which was recorded as Zn-ML.

[0041] The thin-sheet mineral-based all-solid electrolyte prepared in Example 1 and the 2 mol / L zinc sulfate in Comparative Example 1 were assembled into zinc-iodine full batteries. The charge and discharge tests were carried out at a current density of 1 A / g. The performance comparison was as follows: Figure 1As shown, the battery assembled with 2 mol / L zinc sulfate showed a large amount of capacity decay after 500 cycles, while the battery assembled with the thin-sheet mineral-based all-solid electrolyte prepared in Example 1 still maintained a capacity retention rate of up to 80.7% after 2100 cycles.

[0042] The thin-sheet mineral-based all-solid electrolyte prepared in Example 1 and the 2 mol / L zinc sulfate in the comparative example were assembled into zinc-zinc symmetric batteries. 2 After 50 cycles under the charge and discharge conditions, the zinc sheet was tested by XRD. The test results are as follows Figure 2 As shown in the figure, compared with the battery assembled with 2 mol / L zinc sulfate, the battery zinc sheet assembled with the thin sheet mineral-based all-solid electrolyte prepared in Example 1 has almost no by-products generated; at the same time, the zinc negative electrode surfaces of the two were tested by SEM, as shown in the figure. Figure 5 As shown, the zinc negative electrode of the battery assembled with the thin-sheet mineral-based all-solid electrolyte prepared in Example 1 is cleaner and smoother after 50 cycles.

[0043] Example 2

[0044] The method for preparing the mineral-based all-solid electrolyte in this embodiment comprises the following steps:

[0045] Zinc salt electrolyte preparation: dissolve zinc sulfate in deionized water to prepare a zinc sulfate electrolyte with a concentration of 2 mol / L;

[0046] The mullite powder was added into a 2 mol / L zinc sulfate electrolyte at a mass volume ratio of 3:12.5, ultrasonicated for 1 h, stirred for 8 h, then centrifuged, washed twice with deionized water, and then dried at 60 ° C for 12 h to obtain a mineral-based all-solid electrolyte powder;

[0047] The mineral-based all-solid-state electrolyte powder was ground into fine powder in a mortar, 0.1 g of the fine powdered mineral-based all-solid-state electrolyte was weighed, and pressed into 0.3 mm thin sheets of mineral-based all-solid-state electrolyte at a tableting pressure of 20 MPa using a tablet press, which was recorded as Zn-ML-2.

[0048] The thin-sheet mineral-based all-solid electrolyte prepared in Example 2 and the 2 mol / L zinc sulfate in Comparative Example 1 were assembled into zinc-titanium half-cells. LSV tests were performed, and the test results are as follows: Figure 3 As shown, the thin-sheet mineral-based all-solid-state electrolyte prepared in Example 2 significantly inhibited hydrogen and oxygen evolution, and expanded the electrochemical window from 2.27V to 2.7V.

[0049] At the same time, the thin-sheet mineral-based all-solid-state electrolyte prepared in Example 2 was assembled into a zinc-iodine full battery, and a charge and discharge test was carried out at a current density of 1 A / g. After 1800 cycles, the capacity retention rate was still as high as 78%.

[0050] Example 3

[0051] The method for preparing the mineral-based all-solid electrolyte in this embodiment comprises the following steps:

[0052] Zinc salt electrolyte preparation: dissolve zinc acetate in deionized water to prepare a zinc acetate electrolyte with a concentration of 2 mol / L;

[0053] The mullite powder was added into a 2 mol / L zinc acetate electrolyte at a mass volume ratio of 1:10, ultrasonicated for 0.5 h, stirred for 6 h, then centrifuged, washed twice with deionized water, and then dried at 80 ° C for 12 h to obtain a mineral-based all-solid electrolyte powder;

[0054] The mineral-based all-solid-state electrolyte powder was ground into fine powder in a mortar, 0.15 g of the fine powdered mineral-based all-solid-state electrolyte was weighed, and pressed into 0.3 mm thin sheets of mineral-based all-solid-state electrolyte at a tabletting pressure of 30 MPa using a tablet press.

[0055] The thin-sheet mineral-based all-solid electrolyte prepared in Example 3 was assembled into a zinc-iodine full battery. A charge and discharge test was carried out at a current density of 0.75 A / g, and the capacity retention rate was as high as 75% after 1,300 cycles.

[0056] Example 4

[0057] The method for preparing the mineral-based all-solid electrolyte in this embodiment comprises the following steps:

[0058] Zinc salt electrolyte preparation: dissolve zinc sulfate in deionized water to prepare a zinc sulfate electrolyte with a concentration of 2 mol / L;

[0059] The mullite powder was added into a 2 mol / L zinc sulfate electrolyte at a mass volume ratio of 1:15, ultrasonicated for 1 hour, stirred for 24 hours, and then centrifuged, washed four times with deionized water, and then dried at 60°C for 12 hours to obtain a mineral-based all-solid electrolyte powder;

[0060] The mineral-based all-solid-state electrolyte powder was ground into fine powder in a mortar, 0.1 g of the fine powdered mineral-based all-solid-state electrolyte was weighed, and pressed into 0.3 mm thin sheets of mineral-based all-solid-state electrolyte at a tableting pressure of 20 MPa using a tablet press, which was recorded as Zn-ML-4.

[0061] The thin-sheet mineral-based all-solid electrolyte prepared in Example 4 and the 2 mol / L zinc sulfate in Comparative Example 1 were assembled into zinc-zinc symmetric batteries. Electrochemical Tafel tests were performed respectively. The test results are shown in FIG. Figure 4 As shown, the battery assembled with the thin-sheet mineral-based all-solid electrolyte prepared in Example 4 has a smaller corrosion current than the battery assembled with 2 mol / L zinc sulfate.

[0062] Example 5

[0063] The method for preparing the mineral-based all-solid electrolyte in this embodiment comprises the following steps:

[0064] Zinc salt electrolyte preparation: dissolve zinc sulfate in deionized water to prepare a zinc sulfate electrolyte with a concentration of 1 mol / L;

[0065] The mullite powder was added into a 1 mol / L zinc sulfate electrolyte at a mass volume ratio of 1:12.5, ultrasonicated for 2 h, stirred for 6 h, then centrifuged, washed twice with deionized water, and then dried at 60 ° C for 12 h to obtain a mineral-based all-solid electrolyte powder;

[0066] The mineral-based all-solid-state electrolyte powder was ground into fine powder in a mortar, 0.15 g of the fine powdered mineral-based all-solid-state electrolyte was weighed, and pressed into 0.4 mm thin sheets of mineral-based all-solid-state electrolyte at a tabletting pressure of 20 MPa using a tablet press.

[0067] The thin-sheet mineral-based all-solid electrolyte prepared in Example 5 and the 2 mol / L zinc sulfate in the comparative example were assembled into zinc-iodine full batteries. The charge and discharge test was carried out at a current density of 0.5 A / g. The battery assembled with 2 mol / L zinc sulfate showed a large amount of capacity decay after 200 cycles, while the thin-sheet mineral-based all-solid electrolyte prepared in Example 5 maintained a capacity retention rate of up to 85% after 1500 cycles.

[0068] Comparative Example 1

[0069] Zinc sulfate was dissolved in deionized water to prepare a zinc sulfate liquid electrolyte with a concentration of 2 mol / L, recorded as 2MZnSO4.

[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for preparing a mineral-based all-solid electrolyte, characterized in that: The following steps are involved: The mullite powder is mixed with the zinc salt electrolyte, subjected to ultrasonic and stirring treatment, and then centrifugally washed and dried to obtain a mineral-based all-solid electrolyte; The zinc salt electrolyte is at least one of zinc sulfate electrolyte, zinc trifluoromethanesulfonate electrolyte, zinc acetate electrolyte, zinc nitrate electrolyte, and zinc chloride electrolyte; The zinc salt electrolyte concentration is 1 to 3 mol / L; The mass volume ratio of the mullite powder and the zinc salt electrolyte is (1-3.5):(5-15).

2. The method for preparing a mineral-based all-solid electrolyte according to claim 1, characterized in that: The ultrasonic time is 0.5 to 3 hours, and the stirring time is 4 to 24 hours.

3. The method for preparing a mineral-based all-solid electrolyte according to claim 1, characterized in that: The washing times are 2 to 4 times; the drying time is 6 to 12 hours, and the drying temperature is 60 to 100°C.

4. The method for preparing a mineral-based all-solid electrolyte according to claim 2, characterized in that: The following steps are also included: The mineral-based all-solid electrolyte is weighed and tableted using a tablet press to obtain a stable sheet-like mineral-based all-solid electrolyte.

5. The method for preparing a mineral-based all-solid electrolyte according to claim 4, characterized in that: The tablet pressing pressure of the tablet pressing machine is 15-30Mpa.

6. A mineral-based all-solid electrolyte prepared by the preparation method according to any one of claims 1 to 5.

7. Use of the mineral-based all-solid electrolyte according to claim 6 in the preparation of aqueous zinc ion batteries.

8. An aqueous zinc ion battery, characterized in that: The aqueous zinc ion battery comprises a battery housing and a positive electrode, a diaphragm and a negative electrode located in the battery housing, wherein the diaphragm is the mineral-based all-solid electrolyte according to claim 6.